EIN3-Mediated Ethylene Signaling Attenuates Auxin Response during Hypocotyl Thermomorphogenesis. (17th February 2021) - Kim, Jae Young; Park, Young-Joon; Lee, June-Hee; Kim, Zee Hwan; Park, Chung-Mo
Abstract: The gaseous phytohormone ethylene plays vital roles in diverse developmental and environmental adaptation processes, such as fruit ripening, seedling establishment, mechanical stress tolerance and submergence escape. It is also known that in the light, ethylene promotes hypocotyl growth by stimulating the expression of PHYTOCHROME INTERACTING FACTOR3 (PIF3) transcription factor, which triggers microtubule reorganization during hypocotyl cell elongation. In particular, ethylene has been implicated in plant responses to warm temperatures in recent years. However, it is currently unclear how ethylene signals are functionally associated with hypocotyl thermomorphogenesis at the molecular level. Here, we show that ETHYLENE-INSENSITIVE3 (EIN3)-mediated ethylene signals attenuate hypocotyl thermomorphogenesis by suppressing auxin response. At warm temperatures, when the activity of the PIF4 thermomorphogenesis promoter is prominently high, the ethylene-activated EIN3 transcription factor directly induces the transcription of ARABIDOPSIS PP2C CLADE D7 ( APD7 ) gene encoding a protein phosphatase that inactivates the plasma membrane (PM) H + -ATPase proton pumps. In conjunction with the promotive role of the PM H + -ATPases in hypocotyl cell elongation, our observations strongly support that the EIN3-directed induction of APD7 gene is linked with the suppression of auxin-induced cell expansion, leading to the reduction in thermomorphogenic hypocotyl growth. Our data demonstrate that APD7 acts as a molecular hub that integrates ethylene and auxin signals into hypocotyl thermomorphogenesis. We propose that the ethylene–auxin signaling crosstalks via the EIN3-APD7 module facilitate the fine-tuning of hypocotyl thermomorphogenesis under natural environments, which often fluctuate in a complex manner.